Hydrolyzed VCO Cream Reduces Neutrophil Number and Increases Angiogenesis in Mid Dermal Burn Wound Healing - Septin Kamilia Patinggi; Yuriz Bakhtiar; Selamat Budijitno; Neni Susilaningsih; Udin Bahrudin (The Indonesian Biomedical Journal, 2023)
BACKGROUND: Researches on plant active substances are conducted to find effective topical drugs for mid dermal burns wound. The 70% hydrolyzed VCO (hVCO) cream has been known to accelerate macroscopic healing of mid dermal burns compared to 30% and 50% hVCO creams. This study was conducted to further investigate the effectiveness of 70% hVCO cream and find the most effective doses of hVCO to heal mid dermal burns based on the macroscopic diameter, neutrophil number and angiogenesis.METHODS: Thirty mid dermal burns-induced male Rattus norvegicus were randomly divided into 6 groups that were either treated with 70% hVCO cream, 100% hVCO cream, or basic cream for 6 or 12 days. Macroscopic appearance of mid dermal burn was documented, and the diameter was calculated. Hematoxylin Eosin (HE) examination was conducted to measure the neutrophil and angiogenesis in mid dermal burn wound.RESULTS: The decrease of wound macroscopic size was found to be significant after 6 and 12 days of treatment (p=0.004 and p<0.001, respectively), with the smallest diameter was found in 70% hVCO group. The lowest number of neutrophils was found in the 70% hVCO group at day-6 (p=0.039) and day-12 (p=0.013). There was a significant increase of angiogenesis at day-12 (p=0.025) with the highest value obtained in the 70% hVCO group.CONCLUSION: The 70% hVCO decreases the wound macroscopic size, decreases neutrophil number, and increases angiogenesis compared to the 100% hVCO. Hence, 70% hVCO isshown to be the most effective dose in accelerating mid dermal burns wound healing andcan be explored further as topical medication.KEYWORDS: hVCO, neutrophil, angiogenesis, wound healing